2018
DOI: 10.2166/wst.2018.424
|View full text |Cite
|
Sign up to set email alerts
|

Nitric acid-anionic surfactant modified activated carbon to enhance cadmium(II) removal from wastewater: preparation conditions and physicochemical properties

Abstract: The authors used a nitric acid (HNO3)-sodium dodecyl benzene sulfonate (SDBS) method to modify a lignite-based activated carbon. These modified carbons were appraised for their removal of Cd(II) from aqueous solutions. Response surface methodology was employed to optimize the preparation factors including nitric acid concentration CN, temperature T and SDBS concentration CS. Statistical analysis indicated that the interaction of CN and CS incurred the most effect on the maximum cadmium adsorption capacity (Qm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Similarly, Sun et al [24] observed that the BET specific surface area and micro pore volume of a virgin activated carbon, 158 m 2 /g and 0.0804 cm 3 /g increased to 185.07 m 2 /g and 0.0937 cm 3 /g respectively after HNO 3 treatment but reduced to 131.4 m 2 /g and 0.0729 cm 3 treatment with SDBS modification resulted into an increase in the net surface charge of the virgin activated carbon and enhancement in the adsorption capacity.…”
Section: Adsorption Of Inorganic Contaminantsmentioning
confidence: 86%
See 4 more Smart Citations
“…Similarly, Sun et al [24] observed that the BET specific surface area and micro pore volume of a virgin activated carbon, 158 m 2 /g and 0.0804 cm 3 /g increased to 185.07 m 2 /g and 0.0937 cm 3 /g respectively after HNO 3 treatment but reduced to 131.4 m 2 /g and 0.0729 cm 3 treatment with SDBS modification resulted into an increase in the net surface charge of the virgin activated carbon and enhancement in the adsorption capacity.…”
Section: Adsorption Of Inorganic Contaminantsmentioning
confidence: 86%
“…Surface characterisation of virgin activated carbons shows that they have functional groups including carboxyl (R-COOH), phenolic (R-OH) and carbonyl (R = O) [23] [24]. The carbonyl group can complex with inorganic contaminant while the deprotonated acidic functional group can bind heavy metals ions.…”
Section: Sorption Mechanism Of Surfactant Modified Activated Carbonmentioning
confidence: 99%
See 3 more Smart Citations